Regionalisms in Valentina Silantyeva’s Stories “Vilkovo Childhood”: Array - Shykyrynska, Olha (Journal of Danubian Studies and Research, 2020)
The article deals with the research of regional peculiarities of the language and speech of the residents of Vilkovo based on Valentina Silantyeva’s collection of short stories “Vilkovo Childhood” (2013). The significance of regional lexemes, connected with the name of some realities of household activities, toponyms and hydronyms, is analyzed. Regionalisms are the part of local cultural code and define the peculiarities of local identity.